Cardiosphere-derived stem cell culture, characterisation and labelling for in vivo testing in the infarcted heart - Tan, J (2011)
Cardiac stem cells (CSCs), isolated from heart tissue explants and expanded via the formation of cardiospheres (Csp), are a promising candidate for cell therapy to prevent heart failure following myocardial infarction. To allow early administration to patients, isolation and expansion of CSCs must be performed in the shortest time possible. Hence, this project aimed to optimize culture conditions and characterize the cardiac explant-derived cells (EDCs), Csp and Csp-derived cells (CDCs) produced. Rat neonatal EDCs contained 4-7% c-kit+ cells, measured using flow cytometry. Optimal Csp growth conditions were determined, such that plating 3 x 10^4 EDCs per well of a 24-well plate coated with 16.7 µg/ml poly-D-lysine, in CGM containing 7% serum, improved Csp production and generated 1.5 x 10^7 CDCs in 16 days, a sufficient number for cell therapy. The CDCs expressed the stemness markers; c-kit, Oct3/4, SOX2, and Klf-4, and the cardiac differentiation markers; GATA4 and Nkx2.5. The therapeutic effect of CDCs may be limited by the low, 3 ± 0.1%, c-kit+ cell numbers. To increase c-kit+ cells in CDCs, an alternate culture method for Csp and different extracellular matrices (ECM) for cell expansion were tested. The hanging drop culture method produced Csp with higher levels of c-kit+ cells (9 ± 2%) than poly-D-lysine-coated and low-bind culture dishes. Of five ECM tested, collagen IV was found to enhance EDC migration and CDC proliferation, and produced 11 ± 0.4% c-kit+ cells, with Csp cultured in hanging drops. Intramyocardial injection of CDCs improved left ventricular ejection fractions of infarcted rat hearts by 9% and prevented the peri-infarct wall from thinning, measured in vivo using MRI over 16 weeks. To improve cell tracking using MRI, two MR positive contrast agents, gadolinium-DTPA and gadonanotubes were tested. Gd-DTPA had low sensitivity after labelling (1.4 x 10^5 cells/mm2); whereas gadonanotubes did not provide positive contrast at 11.7 T. Thus, neither contrast agent could be used for cell tracking using high magnetic field. In conclusion, CDCs were an effective source of stem cells that could be used for heart repair, although cells could not be tracked using positive MR contrast.